PEMBERDAYAAN EKONOMI PEREMPUAN TANI BERBASIS KELEMBAGAAN - Bambang Susilo (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2010)
Institutional become an empowerment approach pattern lately has been able to lift the poor to be empowered and grow. Communities are organized in a container group (institution), and the group became a learning medium multifunction members at the exchange of information, knowledge, attitude and even to overcome the problem with both economic and social problems. Slowly, the power of individuals will come into force group and that’s where the ongoing process of strengthening and empowerment.